2021
DOI: 10.3389/fpsyt.2021.649095
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Technology Use on Behavior and Sleep Scores in Preschool Children in Saudi Arabia

Abstract: Background: Pre-school children use digital devices both at home and in kindergarten for communication. However, such technologies can also be used for creativity learning and entertainment. Technology usage might exert a negative impact on the psychosocial development of pre-school children, thus necessitating parental monitoring. Previous studies have recommended early intervention for pre-school children by decreasing the duration of digital devices, spending more time with the family, and participation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 33 publications
(40 reference statements)
2
7
0
Order By: Relevance
“…In a high-income country such as Oman, there may be less financial pressure on both parents to work. These findings echo those found in KSA, another high income country in the GCC, where 63% of 3-5 year old children did not attend schools [12]. Even though univariate regression in our study did not show a relationship between child obesity and mother's employment status, the literature on the subject suggests a possible relationship between these two variables.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In a high-income country such as Oman, there may be less financial pressure on both parents to work. These findings echo those found in KSA, another high income country in the GCC, where 63% of 3-5 year old children did not attend schools [12]. Even though univariate regression in our study did not show a relationship between child obesity and mother's employment status, the literature on the subject suggests a possible relationship between these two variables.…”
Section: Discussionsupporting
confidence: 76%
“…Even though univariate regression in our study did not show a relationship between child obesity and mother's employment status, the literature on the subject suggests a possible relationship between these two variables. Studies from the EMR found that mother's unemployment had a negative impact on children's sleep score in KSA and was associated with increased consumption of fast-food meals among middle age children in Oman [12,36]. While a systematic review from low-income countries found no association between maternal employment and obesity, analyses from European countries concluded that mother employment predicted unhealthy dietary, lifestyle patterns and increased BMI among young children [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possible explanation of such result is that disciplinary strategies for child are not necessary require high education level of the father. On the contrary, a study conducted by Almuaigel et al (18) in Saudi Arabia emphasized that father with low education level, work for long time or study for many hours were associated with negative behavior score of their preschool age children.…”
Section: Discussionmentioning
confidence: 88%